Dynamic triggering mechanism of the Pusa mining-induced landslide in Nayong County, Guizhou Province, China. Issue 1 (31st December 2022) - Cui, Fangpeng; Li, Bin; Xiong, Chen; Yang, Zhongping; Peng, Jianquan; Li, Jiangshan; Li, Haowen
Abstract: Catastrophic landslides have occurred frequently in the karst areas of Southwestern China for these years, which makes it urgently necessary to reveal their triggering mechanisms. The universal distinct element code (UDEC) was used to simulate whole response of the Pusa landslide during its underlying coal-seam mining. The results are as follows. First, under the given pre-conditions, when coal seams beneath the original slope were mined from bottom to top, caving zone, fracture zone, and deformation zone overlying the goaf gradually expanded; and as the uppermost layer was mined, the deformation, which was apparently characterized by subsidence and clockwise rotation, overwhelmed the slope. Second, under action of the heavy rainfall, the deformed slope, which was affected by the goaf, behaved further progressive deformation characterized by subsidence and clockwise rotation as a whole. Third, with continuous action of near stoping blasting vibrations, the more-deformed slope, which had been influenced by the goaf and the heavy rainfall, behaved continuous progressive deformation, critical failure, shattering, ejection, debris flow, and accumulation. The deformation exhibited significant subsidence, clockwise rotation, and collapse. These responses were verified by the field reconnaissance. It is the first time to explore dynamic triggering mechanism of the landslide triggered by the vibrations.